Work of the emergency system in polytraumatized patients transferred to the hospital - Auza-Santivañez, Jhossmar Cristians; Condori-Villca, Nayra (Multidisciplinar (Montevideo), 2023)
A descriptive and retrospective observational study of the cases of polytraumatized patients transferred by the emergency medical system to the hospital was carried out, taking into account the work of the emergency system in the transfer of polytraumatized patients in the year 2022. With the aim of highlighting the actions of the emergency system in the face of trauma as a public health problem and its behavior. Percentage analysis was used to express the results, which will be arranged in statistical tables of association of variables and statistical graphs for better analysis and understanding. The main results were that the highest mortality rate was in the series of patients not transferred by the emergency system; of a total of 70 polytraumatized patients, 58 of them were transferred by the emergency system for 82.8% against 12 patients who arrived at the emergency department by other means, of whom the highest percentage corresponded to patients between 40 and 60 years of age, where the main causes were traffic accidents, where the highest number of deaths was in the series of those patients not transferred by the emergency system.